Easy Windows 10 - Soper, Mark Edward (Easy series., 2018)
"See it done. Do it yourself. It's that easy! Easy Windows 10 teaches you the fundamentals to help you get the most from Windows 10. Fully illustrated steps with simple instructions guide you through each task, building the skills you need to perform the most common tasks with Windows. No need to feel intimidated; we'll hold your hand every step of the way, "--Page 4 of cover.